2011
DOI: 10.1590/s0103-50532011000900011
|View full text |Cite
|
Sign up to set email alerts
|

The effects of solar irradiation on copper speciation and organic complexation

Abstract: Este trabalho teve como objetivo avaliar o efeito da irradiação solar na especiação do cobre em amostras de água coletadas em um reservatório eutrofizado e contaminado por metais. Voltametria de redissolução anódica e eletrodo de íon seletivo foram utilizados para determinação de cobre nas amostras irradiadas e não irradiadas. Os resultados demonstraram que após 7 h de irradiação solar, a matéria orgânica dissolvida (DOM) foi degradada promovendo aumento de cobre iônico livre, lábil e de carbono inorgânico dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The excess source here could be due to very weak biological removal combined with a yet undocumented source of dissolved Cu in the surface ocean. A candidate source mechanism is photochemical reactions in the surface ocean, which previous studies have shown can destroy or cleave Cu‐ligand complexes and increase the concentration of free Cu ions (Laglera & ven den Berg, 2006; Moffett & Zika, 1987; Shank et al, 2006; Tonietto et al, 2011). If Cu is photochemically solubilized from colloids or particles larger than 0.2–0.45 μm, this photodegradation could represent a source of dissolved Cu (smaller than 0.2–0.45 μm), as demonstrated by the photo‐dissolution of organic‐associated Cu from resuspended coastal sediments (Skrabal et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The excess source here could be due to very weak biological removal combined with a yet undocumented source of dissolved Cu in the surface ocean. A candidate source mechanism is photochemical reactions in the surface ocean, which previous studies have shown can destroy or cleave Cu‐ligand complexes and increase the concentration of free Cu ions (Laglera & ven den Berg, 2006; Moffett & Zika, 1987; Shank et al, 2006; Tonietto et al, 2011). If Cu is photochemically solubilized from colloids or particles larger than 0.2–0.45 μm, this photodegradation could represent a source of dissolved Cu (smaller than 0.2–0.45 μm), as demonstrated by the photo‐dissolution of organic‐associated Cu from resuspended coastal sediments (Skrabal et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Factors resulting in a negative or mixed effect include photochemical production of inhibitory substances such as hydrogen peroxide (Angel et al, 1999;Baltar et al, 2013;Farjalla et al, 2001;Gjessing and Källqvist, 1991;Kaiser and Sulzberger, 2004;Leunert et al, 2014;Lund and Hongve, 1994;Morris et al, 2011;Scully et al, 2003a;Tranvik and Kokalj, 1998;Weinbauer and Suttle, 1999), release of toxic metals (e.g., Pb, Cu, Ni, Cd, and Hg) from DOM complexes (Haverstock et al, 2012;Tonietto et al, 2011;Winch and Lean, 2005), photolysis of DOM to form substances that are both biologically and photochemically refractory (Kieber, 2000;Stubbins et al, 2010), deactivation of enzymes (Scully et al, 2003b;Vähätalo et al, 2003), changes in the BGE (Abboudi et al, 2008;McCallister et al, 2005;Mopper and Kieber, 2002;Pullin et al, 2004;Smith and Benner, 2005), changes in microbial populations (i.e., community structure) in response to photoproduced substrates or toxic substances (Abboudi et al, 2008;Calza et al, 2008;Lønborg et al, 2013;Piccini et al, 2009), and prior photochemical history, i.e., photon dose-related bleaching (Reader and Miller, 2014). In addition to the above factors, a negative or mixed effect on biological activity can result from reactions of biologically produced ROS, e.g., H 2 O 2 (Palenik and Morel, 1990;Diaz et al, 2013) with photochemically produced reduced metals, e.g., Fe(II), Mn(II), and Cu(I) (Barbeau, 2006;Brinkmann et al, 2003;…”
Section: Coupled Photochemical-microbial Doc Degradation: Impact On Mmentioning
confidence: 99%
“…The photoproduction of labile substrates and mineral nutrients from humic substances may have been offset by the photodestruction of algal-produced DOM (Benner and Biddanda, 1998) or balanced by the photoproduction of toxic substances (Calza et al, 2008;Diamond, 2003;Haverstock et al, 2012;Ortega-Retuerta et al, 2007;Tonietto et al, 2011;Winch and Lean, 2005). Alternatively, carbon limitation may have been important.…”
Section: Coupled Photochemical-microbial Doc Degradation: Impact On Mmentioning
confidence: 99%
“…The photo-induced transformations of DOM could results in: (i) a decrease of DOM concentrations or alteration of its structure and thus increase in the free metal ion concentration and bioavailability [34,50]; (ii) no change in the free metal ion concentrations, because of the production of low molecular weight dissolved organic acids able to scavenge dissolved metal [51]; (iii) an increase of the metal complexation because of a net production of functional groups on humic-like fractions that outcompete for the complexation by low molecular weight dissolved organic acids [34].…”
Section: Consequences For Trace Metal Speciationmentioning
confidence: 99%